2007
DOI: 10.1039/b704977c
|View full text |Cite
|
Sign up to set email alerts
|

Closed-pore crystal capable of adsorbing CO2 onto isolated cavities generated by disorderly mixing of substituents on host skeleton

Abstract: A single crystal adsorbent, [Rh(II)(2)(bza)(4)(2,3-empyz)](n) (2,3-empyz = 2-ethyl-3-methylpyrazine) (1), was synthesized by self-assembly reaction of a Rh(2) benzoate complex and substituted pyrazine linker. The compound consists of one-dimensional zigzag chains, which generated a closed-pore structure without channels. The cavities were statistically generated by the static disorder of substituents on pyrazine and are separated by long intervals within the crystal. The property of CO(2) absorption was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…110 The phase transition and structural transformation of [M 2 (bza) 4 (Rpyz)] can be altered by ligand substitution. 107,113 For example, due to the steric hindrance from the alkyl groups, the 1D chain of [Rh 2 (bza) 4 (empyz)] (empyz = 2-ethyl-3-methylpyrazine) switches from zigzag to straight before and after CO 2 adsorption. 113 Takamizawa et al also observed the precise location of H 2 molecules in [Rh 2 (bza) 4 (pyz)] using in-house SCXRD.…”
Section: Structural Transformation Induced By the Change Of Gaseous G...mentioning
confidence: 99%
“…110 The phase transition and structural transformation of [M 2 (bza) 4 (Rpyz)] can be altered by ligand substitution. 107,113 For example, due to the steric hindrance from the alkyl groups, the 1D chain of [Rh 2 (bza) 4 (empyz)] (empyz = 2-ethyl-3-methylpyrazine) switches from zigzag to straight before and after CO 2 adsorption. 113 Takamizawa et al also observed the precise location of H 2 molecules in [Rh 2 (bza) 4 (pyz)] using in-house SCXRD.…”
Section: Structural Transformation Induced By the Change Of Gaseous G...mentioning
confidence: 99%
“…Crystal-to-crystal transformations are rare but have been observed in other complexes of this type. 47,48 The greater flexibility of these frameworks is thought to have advantages over their more rigid analogues in terms of molecular recognition, separation and sensing applications. 49 In one such system, a tert-butylcalix [4]arene bridged by NH groups, the formation of C-HÁ Á ÁO interactions (2.47-3.17 Å) between the sorbent and CO 2 was deemed necessary for its adsorption.…”
Section: Inclusion Complexes Of Comentioning
confidence: 99%
“…The majority of high-pressure single-crystal diffraction studies on metal complexes have been performed to explore the compressibility of intermolecular and intramolecular interactions or to explore variations in physical properties such as magnetism (Parois et al, 2010;Prescimone et al, 2008Prescimone et al, , 2009; gas absorption (Takamizawa et al, 2005(Takamizawa et al, , 2009Takamizawa & Kohbara, 2007), electrical conductivity (Okano et al, 2004;Guionneau et al, 2003;Rahal et al, 1997) and piezochromism (Byrne et al, 2012). In iron(II) spin-crossover complexes, high-to-low spin transitions have been reported for [Fe(phen) 2 (NCS) 2 ] and [Fe(Btz) 2 (NCS) 2 ] (phen = 1,10phenanthroline, Btz = 2,2 0 -bi-4,5-dihydrothiazine) at 10 and 5 kbar, respectively (Granier et al, 1993).…”
Section: Introductionmentioning
confidence: 99%